Effect of Lime, Humic Acid and Moisture Regime on the Availability of Zinc in Alfisol - Sushanta Kumar Naik; Dilip Kumar Das (The Scientific World Journal)
Lime and humic acid application can play an important role in the availability of zinc in paddy soils. We conducted laboratory incubation experiments on a rice growing soil (Alfisol) to determine the effect of lime, humic acid and different moisture regimes on the availability of Zn. Addition of half doses of liming material (powdered lime stone) recorded highest values of DTPA-Zn followed by no lime and 100% of lime requirement throughout the incubation period. With the progress of incubation, DTPA-Zn increased slightly during the first week and then decreased thereafter. The highest DTPA-extractable Zn content of 2.85 mg/kg was found in the treatment Zn10 L1/2 at 7 days of incubation, showing 17.3 % increase in DTPA-Zn content over its corresponding treatment of Zn alone (Zn10L0). The DTPA-Zn concentration increased with the application of humic acid compared with no humic acid throughout 35 days of the incubation period and the peak value obtained was 3.12 mg/kg in the treatment Zn10 HA2 at 14 days after incubation, showing 50 % increase in Zn content over its corresponding treatment of Zn alone (Zn10HA0). The application of 0.2% humic acid compared with 0.1% resulted in greater increase in DTPA-Zn concentration in soil application. During the 35 days of incubation, highest values of DTPA-Zn were recorded in soil maintained at saturated compared to water logged conditions. However, under alternate wetting and drying condition the DTPA-Zn content gradually decreased up to 21 days and thereafter increased slowly.